F. Scott Barker's Microsoft Access 2000 power programming - Barker, F. Scott (Other Programming Ser., 1999)
Access 2000 Power Programming gives many practical techniques for the corporate and independent developer. New features of Access 2000 are covered thoroughly and useful examples which will be implemented by programmers in their everyday applications. New topics include a chapter devoted to Data Pages, Microsoft's way of bringing the Web interface into everyday office solutions. Also, a new chapter clarifies the confusion over ADP/MDB and DAO/ADO, including when and where to use each. The book covers a number of new additions to VBA which developers will need good exposure to in order to take advantage of them.